3D geometry and architecture of a normal fault zone in poorly lithified sediments: A trench study on a strand of the Baza Fault, central Betic Cordillera, south Spain. (April 2019) - Medina-Cascales, Iván; Koch, Leah; Cardozo, Néstor; Martin-Rojas, Iván; Alfaro, Pedro; García-Tortosa, Francisco J.
Abstract: Successive excavation of 13 trenches of different orientations reveals the complexity of a normal fault zone in Pliocene-Pleistocene unconsolidated sediments on a strand of the Baza Fault, central Betic Cordillera, south Spain. These trenches and the excavation floor are interpreted and integrated to reconstruct the 3D geometry and internal architecture of the fault zone. The structure consists of two main fault strands: an eastern one with a few hundred metres throw and a western one with at least 15 m throw. These strands interact and gradually merge to the south, bounding a main deformation zone narrowing from ∼7 to 1 m along strike. Fault-bounded rock bodies, clay and sand smears, and clay injections define the structure. These features are highly variable in 3D. In the northern part of the outcrop, deformation is localized around the main strands, brittle in the west and more ductile to the east. As the strands and their fault zones increasingly interact, fault throw, rock deformation and maturity of the structure increase. Mechanical stratigraphy also controls the style of deformation. A realistic representation of this 4D picture of fault deformation is critical for modelling fluid flow in shallow to possibly deep, faulted sedimentary reservoirs. Highlights: A 3D trench study reveals the complexity of a normal fault zone in soft sediments. Highly variable rock bodies, faults, smears and clay injections form the fault zone. Variable fault geometries and throws cause a variable distribution of deformation. Mechanical stratigraphy has a key role in the variability and style of deformation. As main strands approach, fault throw, deformation and fault zone maturity increase.